Conversion of Mangroves Into Rice Cultivation Alters Functional Soil Microbial Community in Sub-Humid Tropical Paddy Soil - Kumar, Upendra; Kaviraj, Megha; Panneerselvam, P.; Nayak, A. K. (Frontiers in Environmental Science, 2022)
Conversion of mangroves vegetation into rice cultivation is considerably enhanced nowadays which affected adversely the ecological sustainability. Soil microbial community is one of the key indicators to monitor soil health in mangroves. Studies on variations in the microbial community within mangroves are plenty, whereas reports in mangrove-converted paddy soils are scarce. Therefore, Biolog® eco-plate-based technique was used in this study to assess soil microbial community in the Bhitarkanika (MB) and Sundarban (MS) sub-humid tropical mangroves-converted paddy soil. The results showed that significantly lower soil microbial biomass carbon and enzyme activities were recorded in MB and MS compared to NRRI (National Rice Research Institute) paddy soil where continuous rice cultivation is being practiced conventionally since 1946 under the sub-humid tropical region. Biolog®-based average well color development (AWCD) was found significantly lower in MS and MB compared to NRRI. Shannon-Weaver and McIntosh indices followed similar trends of AWCD. Biplot analysis indicated the positive correlation of pH, available phosphorus, actinomycetes population, and phenolic compound utilization under MS, whereas EC and phosphate-solubilizing bacteria were positively correlated under MB. Compared to MS and MB, NRRI paddy soil harbored more carbohydrate-utilizing microbes and showed a positive correlation with fluorescin-diacetate, dehydrogenase, and acid phosphatase. Overall, the present study suggested that the conversion of the Sundarban and Bhitarkanika mangroves into rice cultivation adversely affected the microbial diversity thereby altering their natural sustainability.